1999
DOI: 10.1177/135245859900500103
|View full text |Cite
|
Sign up to set email alerts
|

The fatigue descriptive scale (FDS): a useful tool to evaluate fatigue in multiple sclerosis

Abstract: Although fatigue is common among multiple sclerosis (MS) patients, evaluation of this symptom is difficult due to the subjectivity and variability of the complaint. We proposed the Fatigue Descriptive Scale (FDS) as a tool to evaluate the severity and quality of fatigue in a group of patients suffering from MS. As a way to demonstrate the usefulness of this scale we applied the FDS in a group of 155 patients (105 women and 50 men) with clinically-definite multiple sclerosis, as outlined according to Poser's cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 32 publications
0
41
1
Order By: Relevance
“…Some scales are applicable for several types of fatigue, and some scales measure fatigue caused by a specific disease. [11][12][13][14][15] No scale has yet been developed specifically for poststroke fatigue. Most studies use multidimensional self-estimation questionnaires to measure poststroke fatigue.…”
mentioning
confidence: 99%
“…Some scales are applicable for several types of fatigue, and some scales measure fatigue caused by a specific disease. [11][12][13][14][15] No scale has yet been developed specifically for poststroke fatigue. Most studies use multidimensional self-estimation questionnaires to measure poststroke fatigue.…”
mentioning
confidence: 99%
“…The subjective experience of fatigue is multifactorial and has been correlated with factors such as disability, depression, and pain. [5][6][7] Interestingly, no clear association has been established between MS fatigue and demographic factors, such as age and gender; lesion burden; or the clinical form of MS. 1,[7][8][9] ABSTRACT: Background: Fatigue is common and disabling in multiple sclerosis, yet its physiologic substrates remain poorly defined. The aim of this study was to determine the relationship between fatigue and an objective measure of alertness in MS patients.…”
mentioning
confidence: 99%
“…The Fatigue Descriptive Scale (FDS) 8 is a tool developed to evaluate the periodicity, severity, and quality of fatigue caused by MS. Based on the subject's responses, a score of 0 to 3 is assigned to each of the categories of initiative, modality, frequency, severity, and fatigue associated with heat. The FDS has been shown to be highly correlated with the FSS.…”
Section: Fatigue Descriptive Scalementioning
confidence: 99%
“…The room should be kept cool, because it has been shown that an increase in environmental temperature increases fatigue. 3,6,8,17 The use of air conditioning is highly recommended for individuals with MS and has been approved by some health insurance plans as a funded medical requirement. In Canada, the purchase of an air conditioner for individuals with MS has been accepted as a medical requirement and is therefore a taxdeductible item.…”
Section: Modification Of Environmentmentioning
confidence: 99%